A Review: The Performance of Reinforced Concrete Beam Containing Palm Oil Fuel Ash and Metakaolin Subjected to Four-Point Bending Test. - Triman Rakasiwi, Dini Reka Azmaningtias; Ismail M.H., (Recent Trends in Civil Engineering and Built Environment, 2021)
The extreme lack of raw materials has been the challenge facing the construction sector in recent days. It is every duty to reduce the environmental impact of the development of construction products. The perfect approach to achieving sustainable growth in the concrete sector is the use of waste and by-product materials in a concrete mix of renewable resources. In this study, the conventional concrete mix design was modified using POFA and MK as cement substitute material to understand structural behavior and compressive strength. Different percentages of POFA and MK in concrete show positive results for strength and durability.